Factors Associated with Household Transmission of Pandemic (H1N1) 2009 among Self-Quarantined Patients in Beijing, China - Zhang, Daitao (Public Library of Science, 2013)
As the pandemic (H1N1) 2009 progressed, the Ministry of Health of China advised cases with mild symptoms to remain home for isolation and observation, which may have increased the risk for infection among other household members. Describing the transmission characteristics of this novel virus is indispensable to effectively controlling the spread of disease; thus, the aim of this study was to assess risk factors associated with household transmission of pandemic H1N1 from self-quarantined patients in Beijing, the capital city of China. A 1:2 case-control study with 54 case households and 108 control households was conducted between August 1 and September 30, 2009 in Beijing. Cases were households with a self-quarantined index patient and a secondary case, while controls were households with a self-quarantined index patient and a close contact. Controls were also matched to cases for sex and age of index case-patient. A structured interview guide was used to collect the data. Conditional logistical models were employed to estimate Odds Ratios (OR) with 95% confidence intervals (95% CI). Results indicated that higher education level (OR 0.42; 95% CI 0.22-0.83), sharing room with an index case-patient (OR 3.29; 95%CI 1.23-8.78), daily room ventilation (OR 0.28; 95%CI 0.08-0.93), and hand washing ≥3/d (OR 0.71; 95%CI 0.48-0.94) were related to the household transmission of pandemic H1N1 from self-quarantined patients. These results highlight that health education, as well as the quarantine of the index case-patient immediately after infection, frequent hand hygiene, and ventilation are critical to mitigating household spread of pandemic H1N1 virus and minimizing its impact. Household contacts should be educated to promote these in-home practices to contain transmission, particularly when household members are quarantined at home.